Da'wah Content on Social Media Towards Increasing Islamic Character Building: An Analysis of Student Perceptions - Destriafiani, Mellysa; Halim, Sahril; Ahyar, Ahyar; Khan, Shabeer (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
In the digital era, social media is one of the main means of spreading da'wah that has the potential to affect the Islamic character of individuals, especially among students. This study aims to reveal how the consumption of da'wah content on social media plays a role in shaping the Islamic character of students and explore whether there are differences in perceptions based on gender in responding to the influence of digital da'wah. The study used a quantitative approach research method, where data were collected using a Likert scale questionnaire and analyzed using multiple linear regression tests and t-tests (Independent Samples t-tests) with a sample of 112 students from several universities in West Nusa Tenggara (NTB) Province. The results showed that there was a significant relationship between the consumption of da'wah content on social media and the formation of Islamic character which contributed 59.4%. In addition, this study did not find any significant differences in student perceptions based on gender towards the influence of digital da'wah content in Islamic character formation. The implications of these findings highlight the importance of utilizing the use of social media as an effective means of da'wah in shaping students' Islamic character.